Root and tuber crops in Dominica, West Indies - Sorhaindo, C.A. (International Center for Tropical Agriculture, 1986)
An analysis is made of both the land available for 6 root crops- -Colocasia esculenta, Xanthosoma sagittifolium, yam, sweet potato, cassava, and white potato--and the land potential for crop expansion, estimated to be 50 percent over the next 4 yr. Farm characteristics and cropping systems involving these crops are also described. The production costs of these crops are considered high, and therefore restrict their demand. Likewise, the major constraints on domestic and external demand are considered, and the future policy directions that should be followed to counteract these restrictions are discussed. Finally, the role that the research institutions can play in greater crop development is discussed. At the community level, cassava is processed into farina. (CIAT)